2021
DOI: 10.1177/13524585211039104
|View full text |Cite
|
Sign up to set email alerts
|

Exploring CSF neurofilament light as a biomarker for MS in clinical practice; a retrospective registry-based study

Abstract: Background: Neurofilament light (NFL) has been increasingly recognized for prognostic and therapeutic decisions. Objective: To validate the utility of cerebrospinal fluid NFL (cNFL) as a biomarker in clinical practice of relapsing-remitting multiple sclerosis (RRMS). Methods: RRMS patients ( n = 757) who had cNFL analyzed as part of the diagnostic work-up in a single academic multiple sclerosis (MS) center, 2001–2018, were retrospectively identified. cNFL concentrations were determined with two different immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…This is further evidenced by the transient increase in the CSF NfL. CSF NfL is currently being studied as a marker in neurodegenerative diseases [ 100 102 ] and pre-clinical animal models of HD [ 103 ]. NfL has also been found in higher concentrations in plasma and CSF of HD and pre-HD patients and is thought to be related to neuronal cell death [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is further evidenced by the transient increase in the CSF NfL. CSF NfL is currently being studied as a marker in neurodegenerative diseases [ 100 102 ] and pre-clinical animal models of HD [ 103 ]. NfL has also been found in higher concentrations in plasma and CSF of HD and pre-HD patients and is thought to be related to neuronal cell death [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different studies documented a significant relationship between age and CSF, serum, and plasma NfL in MS [ 40 , 156 , 278 , 287 ]. The association between NfL and gender is also controversial; most studies found no relationship between CSF and serum NfL and sex [ 40 , 271 , 287 , 288 ]. On the other hand, a cohort reported higher serum NfL levels in females [ 289 ], while according to other studies, CSF NfL concentrations were more prominent in male patients [ 290 , 291 ].…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
“…Ultimately, in case of uncertainty, measurement of NfL might be utilised as a complementary examination to distinguish patients at risk of developing CDMS from non-converters. In addition to identifying CIS patients with a risk of future conversion, higher baseline CSF NfL is associated with disease severity [ 263 ], future EDSS progression and conversion to SPMS [ 288 , 290 ]. Data in the literature suggests that not baseline [ 263 ] serum NfL but the change in its level indicates future conversion to SPMS [ 301 ].…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
See 2 more Smart Citations